The neurohormone tyramine stimulates the secretion of an insulin-like peptide from the Caenorhabditis elegans intestine to modulate the systemic stress response. - Tania Veuthey; Jeremy T Florman; Sebastián Giunti; Stefano Romussi; María José De Rosa; Mark J Alkema; Diego Rayes (PLoS Biology)
The DAF-2/insulin/insulin-like growth factor signaling (IIS) pathway plays an evolutionarily conserved role in regulating reproductive development, life span, and stress resistance. In Caenorhabditis elegans, DAF-2/IIS signaling is modulated by an extensive array of insulin-like peptides (ILPs) with diverse spatial and temporal expression patterns. However, the release dynamics and specific functions of these ILPs in adapting to different environmental conditions remain poorly understood. Here, we show that the ILP, insulin-3 (INS-3), plays a crucial role in modulating the response to various environmental stressors in C. elegans. ins-3 mutants display increased resistance to heat, oxidative stress, and starvation; however, this advantage is countered by slower reproductive development under favorable conditions. We find that ins-3 expression is downregulated in response to environmental stressors, whereas, the neurohormone tyramine, which is released during the acute flight response, increases ins-3 expression. We show that tyramine induces intestinal calcium (Ca2+) transients through the activation of the TYRA-3 receptor. Our data support a model in which tyramine negatively impacts environmental stress resistance by stimulating the release of INS-3 from the intestine via the activation of a TYRA-3-Gαq-IP3 pathway. The release of INS-3 systemically activates the DAF-2 pathway, resulting in the inhibition of cytoprotective mechanisms mediated by DAF-16/FOXO. These studies offer mechanistic insights into a brain-gut communication pathway that weighs adaptive strategies to respond to acute and long-term stressors.